CLINICAL EVALUATION OF AYURVEDIC FORMULATION OF COLICARMIN PLUS SYRUP ON COLIC, GRIPING PAIN, INDIGESTION, NAUSEA, VOMITING, AND OTHER DIGESTIVE DISORDERS IN PAEDIATRICS AND GERIATRICS PATIENTS. - H Patel, Girish; Mishra, Devendra; Gathani, Rupali (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: An open label study to assess the effect of colicarmin plus syrup on colic and griping pain, indigestion, nausea and vomiting in children, and geriatric patients. Methods: (a) A study was conducted on 75 number of patients to evaluate the effect of colicarmin plus syrup on colic and griping pain, indigestion, nausea and vomiting in children, and adults, (b) mostly these children were selected from different classes of families, (c) all the patients were checked on the 1 st , 2 nd , and 3 rd week after starting the therapeutic dose. Dosage schedule: (a) Children: 1 Teaspoonful thrice a day after meals, (b) adults: 2 Teaspoonful twice to thrice a day after meals. Results: (a) Colic and griping pain: In the total duration of treatment, no of patients recovering were 23-on 1 st week, 4-on 2 week, overall result is 93.54%, (b) indigestion: In the total duration of treatment, no of patients recovering were 26-on 1 st nd week, and 3-on 3 week, 3-on 2 week, and 1-on 3 rd week, the overall result is 93.75%, (c) nausea and vomiting: In the total duration of treatment, no of patients recovering were 8-on 1 week, 2-on 2 nd week, and 1-on 3 rd week, the overall result is 91.33%. Conclusion: Based on the study, we can conclude that colicarmin plus syrup is an Ayurvedic formulation with benefits such as digestive, carminative, anthelmintic, antiflatulent, antispasmodic, and devoid of side effects. Keywords: Digestive, Carminative, Anthelmintic, Antiflatulent and Antispasmodic. nd st rd